Evaluation of intralesional injection of hyaluronic acid compared with verapamil in Peyronie's disease: preliminary results from a prospective, double‐blinded, randomized study. (July 2017) - Favilla, V.; Russo, G. I.; Zucchi, A.; Siracusa, G.; Privitera, S.; Cimino, S.; Madonia, M.; Cai, T.; Cavallini, G.; Liguori, G.; D'Achille, G.; Silvani, M.; et al.
Summary: Several intralesional therapeutic protocols have been proposed for the treatment of Peyronie's disease. Among all, hyaluronic acid (HA) and verapamil have been differently tested. We aimed to evaluate the efficacy of intralesional verapamil (ILVI) compared with intralesional HA in patients with early onset of Peyronie's disease (PD). This is a multi‐centre prospective double‐arm, randomized, double‐blinded study comparing ILVI vs. intralesional HA after 12‐weeks. Sexually active men, older than 18 years and affected by the acute phase of PD were eligible for this study. Patients have been double‐blinded randomly divided into two groups (1 : 1 ratio): Group A received intralesional treatment with Verapamil (10 mg in 5 mL of normal saline water) weekly for 12 weeks, while group B received intralesional treatment with HA (0.8% highly purified sodium salt HA 16 mg/2 mL) weekly for 12 weeks. The primary efficacy outcome was the change from the baseline to the endpoint (12 weeks after therapy) for the penile curvature (degree). The secondary outcome was the change in the plaque size and in the International Index of erectile Function (IIEF‐5) score. The difference between post‐ and pre‐treatment plaque size was −1.36 mm (SD ± 1.27) for Group A and −1.80 mm (SD ± 2.47) for Group B ( p ‐value = NS). IIEF‐5 increased of 1.46 points (SD ± 2.18) in Group A and 1.78 (SD ± 2.48) in Group B ( p ‐value ± NS). No difference in penile curvature was observed in Group A, while in Group B the penile curvature decreased of 4.60° (SD ± 5.63) from the baseline ( p  < 0.001) and vs. Group A. According to PGI‐I results, we found significant difference as concerning patient global impression of improvement (PGI‐I) (4.0 vs. 2.0; p  < 0.05). This prospective, double‐arm, randomized, double‐blinded study comparing ILVI vs. HA as intralesional therapy showed greater efficacy of HA in terms of penile curvature and PGI‐I.